2005
DOI: 10.1016/j.febslet.2005.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the angiogenesis by the MCP‐1 (monocyte chemoattractant protein‐1) binding peptide

Abstract: The CC chemokine, monocyte chemoattractant protein-1 (MCP-1), plays a crucial role in the initiation of atherosclerosis and has direct effects that promote angiogenesis. To develop a specific inhibitor for MCP-1-induced angiogenesis, we performed in vitro selection employing phage display random peptide libraries. Most of the selected peptides were found to be homologous to the second extracellular loops of CCR2 and CCR3. We synthesized the peptide encoding the homologous sequences of the receptors and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
(35 reference statements)
1
26
0
Order By: Relevance
“…According to our observations, MCP-1 is not associated with tumour mass, and this chemokine does not promote production of inflammatory proteins. MCP-1 is the first CC chemokine reported to play a direct role in tumour angiogenesis [23], and some studies describe possible mechanisms by which this chemokine induces angiogenesis [24,25]. Results of our immunohistochemical analysis are in accordance with this observation, since microvessel density and macrophage level were higher in high-grade than in low-grade lymphomas as observed in previous studies [26].…”
Section: Discussionsupporting
confidence: 95%
“…According to our observations, MCP-1 is not associated with tumour mass, and this chemokine does not promote production of inflammatory proteins. MCP-1 is the first CC chemokine reported to play a direct role in tumour angiogenesis [23], and some studies describe possible mechanisms by which this chemokine induces angiogenesis [24,25]. Results of our immunohistochemical analysis are in accordance with this observation, since microvessel density and macrophage level were higher in high-grade than in low-grade lymphomas as observed in previous studies [26].…”
Section: Discussionsupporting
confidence: 95%
“…Gharaee-Kermani et al [28] showed that MCP-1 promotes collagen expression by fibroblasts in a transforming growth factor b-dependent manner. Recently, MCP-1 has been recognized as an angiogenic chemokine [29][30][31]. Salcedo et al [30] showed that the angiogenic effect of MCP-1 does not require inflammatory leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ongoing studies have also determined that imposition of a chronic exercise regimen can have the beneficial impact of blunting the severity of this inflammatory condition and can include reductions in the levels of C-reactive peptide, IL-1␤, tumor necrosis factor-␣, and IL-6 (18,42,48). To investigate the correlation between the genesis of the metabolic syndrome and the regulation of skeletal muscle microvessel density in response to chronic exercise, we determined levels of inflammatory cytokines associated with angiogenesis within the setting of cancerous tumor progression [IL-13 (16,33,34), MCP-1 (25,27,28,33), and IL-1␤ (9, 41, 54)]. As presented in Fig.…”
Section: Discussionmentioning
confidence: 99%